(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2017)
Doing business based on the concept of the CSR could lead to competitive advantage, especially through image improvement, higher customer loyalty, increasing motivation and satisfaction of employees and attracting investments. The pressure which different stakeholders put on Serbian companies is incomparably lower than in developed countries. At the same time, socially responsible companies are not sufficiently recognized at domestic market. Implementation of CSR is relevant for investors also, because investors beside financial indicators pay attention to companies’ behavior in society and its contribution to social goals. CSR report is the primary communication tool used to indicate company’s CSR strategy and actions concerning its’ social and environmental commitment. The weakest point in CSR systems of Serbian companies is reporting about non-financial performances. This paper is a result of comparative analysis of CSR reports of Serbian companies (15 companies). The main goals were to show which fields companies consider the most relevant and how they contribute to social problems solving. Given that CSR reporting is not mandatory, large number of companies does not prepare CSR reports, because they do not realize the need and the purpose of these reports. The results could raise awareness about CSR reporting among Serbian companies. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.